Salt content in spice mixtures of selected producer on the Polish market - Śmiechowska, Maria; Drozd, Monika (Zawartość soli w mieszankach przyprawowych wybranych producentów na polskim rynku, 2021)
Spice mixtures are very popular additives used in food technology and households. They consist of salt (understood as the content of sodium chloride (NaCl)) and vegetables, as well as substances influencing sensory properties, such as those enhancing the taste and aroma and affecting the general appearance and texture of spices. The main aim of the study was to assess the salt content of traditional, conventional spice mixtures in comparison with a new line of spice herb mixtures produced by two leading companies on the Polish market. The traditional mixtures contained salt in a very wide-ranging amounts, from trace amounts to over 50 g salt/100 g of product. Spice herbs produced by both companies did not contain salt. An additional aim of the study was to present ways of dietary salt intake reduction through educational programmes and the implementation of innovative spice mixtures with a reduced salt content or salt-free spice products.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2021, Nr 37, s. 171-181
Keywords: spices; salt content; products innovations; przyprawy; zawartość soli; innowacje produktowe